The Conservation Reserve: A Survey of Research and Interest Groups - Hughes, Jennie S.; Hoag, Dana L.; Nipp, Terry E. (Council for Agricultural Science and Technology (CAST), 1995)
This CAST Report summarizes Conservation Reserve Program (CRP) policy literature and a survey of key special interest groups regarding their preferences for a future CRP. By gathering key literature and preference information into a single document, the Task Force authors are able to present and evaluate options for the future.